Inovação sustentável em modelos de negócios de impacto - Müller, Liara de Oliveira (2021)
The business world has become an increasingly complex and demanding space, considering the global context, with many instabilities, new technologies, crises, many market variations, which brings a series of challenges for companies of all postage. When considering the relevance of the role of organizations in contemporary society, the importance of understanding sustainable innovations in impactful business models emerged, which can contribute to the mitigation of current social problems and allow organizations to survive in an increasingly market. competitive. The focus of this study was impact business models, which consist of enterprises whose main purpose is to solve a social problem using sustainable business methods and were based on authors such as Barki (2015) and Yunus, Moingeon, Lehmann- Ortega (2010). The objective of the study was defined to analyze sustainable innovations in impact business models and, to achieve this objective, a qualitative exploratory approach was used, with the application of semi-structured interviews and document analysis in four organizations that are willing to participate of the research. The results found allowed us to identify the main evidence related to the elements of sustainable innovation, highlighting the fact that they all practice innovations in terms of maximizing energy and water efficiency, with the help of solar panels and water reuse. In contrast, the study revealed that none of the organizations develop large-scale sustainable solutions to maximize social and environmental benefits, as they consider themselves small. The study also contributed to understanding and identifying which paths of sustainable innovations impact business models are adopting, how they established new strategies, new processes and habits and how this potential model can be replicated, adding social and environmental aspects and, being profitable on an equitable basis. Amidst all these questions, the perception of organizations regarding the Covid-19 pandemic was obtained, what are the challenges regarding human and business relations, what is the capacity for reinvention that the surveyed organizations highlighted in this pandemic period, and showed that It is noted that none had their business model changed as a result of the pandemic. The companies readjusted in terms of operations and all highlighted the growth of their business in the last year, showing enthusiasm amidst the global crisis.